2018
DOI: 10.3171/2018.4.peds17607
|View full text |Cite
|
Sign up to set email alerts
|

Seizure outcome in pediatric medically refractory temporal lobe epilepsy surgery: selective amygdalohippocampectomy versus anterior temporal lobectomy

Abstract: OBJECTIVEThe aim of this study was to investigate long-term seizure outcome, rate of reoperation, and postoperative neuropsychological performance following selective amygdalohippocampectomy (SelAH) or anterior temporal lobectomy (ATL) in pediatric patients with medically refractory temporal lobe epilepsy (TLE).METHODSThe authors performed a retrospective review of cases of medically refractory pediatric T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…43 A nonsignificant tendency toward a worse visual memory outcome after ATL, especially after right-sided surgery, was reported by Tanriverdi et al and Morino et al 47,51 In contrast, a significant improvement in figural memory performance was found in four studies with a tendency towards left-sided surgery. 48,49,51,52 A decline in naming ability was reported by Engel et al in 55% (6/11) of patients after ATL. 37 In contrast, Sagher et al did not find significant changes in Boston Naming Test scores after either ATL or sAHE.…”
Section: Neuropsychological Outcomementioning
confidence: 85%
See 2 more Smart Citations
“…43 A nonsignificant tendency toward a worse visual memory outcome after ATL, especially after right-sided surgery, was reported by Tanriverdi et al and Morino et al 47,51 In contrast, a significant improvement in figural memory performance was found in four studies with a tendency towards left-sided surgery. 48,49,51,52 A decline in naming ability was reported by Engel et al in 55% (6/11) of patients after ATL. 37 In contrast, Sagher et al did not find significant changes in Boston Naming Test scores after either ATL or sAHE.…”
Section: Neuropsychological Outcomementioning
confidence: 85%
“…Finally, 13 studies dealing with MRgLITT [21][22][23][24][25][26][27][28][29][30][31] and six dealing with RFA [32][33][34][35][36] were included (Figure 1). For ATL and sAHE, four RCTs 4,37-39 and 20 comparative studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Favorable seizure outcome also positively influences the postoperative IQ, although the impact of seizure control is still controversial regarding memory tasks 5,39 . The manner in which the extent of the resection impacts neurocognitive performance following TLE surgery is also not clear, as there are studies reporting no differences between nonselective and selective approaches and no memory decline following nonselective resection in some subgroups of patients 5,40,41 . It is important to note that late postoperative structural MRIs showed prominent atrophy and increased T2‐weighted signal in the temporal pole after selective transsylvian amygdalohippocampectomies (TI‐AH and TU‐AH) 3,16 .…”
Section: Discussionmentioning
confidence: 99%
“…TLE is the most complex partial epilepsy syndrome which will eventually develop into intractable seizures as patients become resistant to treatment drugs [18]. TLE generally occurs in childhood and recurs many times throughout life, although some pediatric TLE patients do benefit from acceptable and safe resection [19,20]. TLE is accompanied by long-term language impairment, cog- nitive decline, and even memory deficits, all of which diminish the quality of social events and life [21][22][23].…”
Section: Discussionmentioning
confidence: 99%